Do airline pilots and cabin crew have raised risks of melanoma and other skin cancers? Systematic review and meta‐analysis4. (18th March 2019) - Miura, K.; Olsen, C.M.; Rea, S.; Marsden, J.; Green, A.C.
Summary: Background: Airline pilots and cabin crew are potentially exposed to hazardous ultraviolet and cosmic radiation, which may increase their risk of melanoma and other skin cancers. Objectives: To establish precise risks of melanoma and keratinocyte cancer (KC) for airline pilots and for cabin crew based on all studies published to date. Methods: We searched MEDLINE, ISI Science Citation Index, Embase, SCOPUS and CINAHL to June 2018. All studies of melanoma and KC risk and mortality in airline pilots and cabin crew compared with the general population were eligible. Standardized incidence ratios (SIRs) and standardized mortality ratios (SMRs) were pooled using random effects models. Results: From 5866 papers retrieved, we reviewed 44 full‐text articles, of which 12 studies with data collected mostly between the 1970s and 1990s were eligible for inclusion. The pooled SIR (pSIR) for melanoma in pilots was 2.03 [95% confidence interval (CI) 1.71–2.40] and in cabin crew it was 2.12 (95% CI 1.71–2.62). For pilots, the pooled SMR for melanoma was 1.99 (95% CI 1.17–3.40) and for cabin crew it was 1.18 (95% CI 0.73–1.89). For KC, the pSIR was 1.86 (95% CI 1.54–2.25) in pilots and 1.97 (95% CI 1.25–2.96) in cabin crew. There was no evidence of study heterogeneity. Conclusions: The available evidence shows that airline pilots and cabin crew have about twice the risk of melanoma and other skin cancers than the general population, with pilots more likely to die from melanoma. However, most of the evidence was collected several decades ago and their relevance to contemporary levels of risk is uncertain. Abstract : What's already known about this topic? Airline pilots are exposed to cosmic and ultraviolet (UV) radiation in their occupations, and cabin crews are occupationally exposed to cosmic radiation. Airline pilots and cabin crews appear to be at significantly increased risk of developing melanoma; pilots are at increased risk of dying from melanoma. What does this study add? Risk of melanoma and other skin cancers is approximately doubled in airline pilots and cabin crew compared with the general population; occupational exposure to UV is unlikely to explain the raised risk. Causal roles of occupational exposure to ionizing radiation and recreational exposure to UV are plausible, but there is little supporting evidence. Almost all relevant evidence is out of date and is restricted to the northern hemisphere; research is needed that better reflects the occupational environment and recreational behaviour of current pilots and cabin crews. Plain language summary available online